Implications of managed life and civil war on the political thinking of Arendt and Agamben - Cruz, Daniel Nery da (Argumentos - Revista de Filosofia, 2019)
In this article we will make an investigation about the life managed in Hannah Arendt and Giorgio Agamben, elaborating an understanding of the political philosophy of the two authors in the conception that each one develops on the civil war and the political space. For this, we will highlight how Arendt relates political life to a public liberty of the people and not an inner freedom based on philosophical contemplation. Freedom and revolution are closely intertwined for the understanding of politics. On the concept of civil war in his work On the Revolution, Arendt affirms that it is necessary to deny the naturalization of equality and any form of alienating power. When the revolution is directed in a way that is not life, but the democratic principles and institutions that are the centrality, there is a space for the new, for political action or what we call anarchic action. The understanding of the notion of life and its relation to politics is the debate Arendt makes about civil war or revolution, so we have also sought to reflect on what Agamben calls the stasis or civil war in Greek and how he interprets the biopolitics with this concept, even with a critique of Arendt herself by the confusion between the concepts of revolution and war.